A relação do envelhecimento com a audição e a cognição - Bruckmann, Mirtes (2019)
Objective: To analyze an aging relation with hearing and cognition. Still, as specific objectives, to analyze the influence of mild hearing loss, cognition and aging in the behavioral tests of Central Auditory Processing (CAP); todescribe and compare Mismatch Negativity (MMN) in elderly presenting normal hearing and hearing loss and correlate it with the cognitive and behavioral aspects of CAP in these groups and also, to generate normality values for MMN in the elderly; to analyze the characteristics of Long Latency Auditory Evoked Potentials (LLAEP), P1, N1, P2, N2, P300 and MMN and their occurrence in aging. Method: Participated 54 elderly people aged between 60 and 77 years. Of these, 33 were normal-hearing and 21 presented mild hearing loss. Also participated 20 normal hearing adults, aged between 18 and 35 years. All performed anamnesis, basic audiological assessment, Montreal Cognitive Assessment (MoCA), Dichotic Digit Test (DDT), Speech in Noise test (SN) and the Randon Gap Detection Test (RGDT) and even the LLAEP elicited with verbal stimuli ba/ di for P1, N1, P2, N2 and P300 and with stimulation da/ ta for MMN, performed on SmartEP. The presence and absence of potentials was analyzed and, when present, the latency value of all potentials was analyzed, as well as the amplitude and duration of the P300 and MMN and the MMN area. Results: there was a significant difference between the elderly with and without hearing loss for DDT in the left ear (LE) and in the SN. The MoCA correlated with RGDT and DDT. The elderly had worse results in the CAP tests than adults. The LLAEPs were not affected by hearing loss. There was a correlation between the amplitude of the MMN with the RGDT and DDT and the altered DDT increased the duration of the MMN. The P2 latency was higher in the elderly and MMN latency was lower. The MMN showed more absences in the elderly. Conclusion: The mild hearing loss affected the responses of the SN test and the DDT, without influences on the RGDT, MoCA and LLAEP. Cognitive aspects correlated with RGDT and DDT, but not with MMN. The SN test was the only behavioral test that demonstrated only auditory results, without influences of cognition and aging was able to cause impairments in the CAP tests. The alteration in the CAP was able to cause longer durations in the MMN. It was possible to generate normality values for MMN in elderly people aged 60 to 77 years who are normal-hearing or present mild hearing loss, being the average latency value 199.8ms, amplitude 2.2μV, area 116.1μVms and duration 81.2ms. Among the LLAEP, P2 and MMN were more affected by aging.